1993
DOI: 10.1126/science.8475383
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Basis for Specific Recognition of Both RNA and DNA by a Zinc Finger Protein

Abstract: Transcription factor IIIA (TFIIIA) from Xenopus oocytes binds both the internal control region of the 5S ribosomal RNA genes and the 5S RNA transcript itself. The nucleic acid binding domain of TFIIIA contains nine tandemly repeated zinc finger motifs. A series of precisely truncated forms of this protein have been constructed and assayed for 5S RNA and DNA binding. Different sets of zinc fingers were found to be responsible for high affinity interactions with RNA and with DNA. These results explain how a sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
113
0

Year Published

1994
1994
2011
2011

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(120 citation statements)
references
References 34 publications
7
113
0
Order By: Relevance
“…One of the best studied is the TFIIIA transcription factor, which contains zinc finger modules specialized for either DNA or RNA recognition. Some of these modules provide the majority of the protein binding affinity for DNA, whereas the others form specific complexes with their RNA targets (47)(48)(49). Thus, zinc fingers differ somewhat in ability to bind tightly to DNA and RNA.…”
Section: Discussionmentioning
confidence: 99%
“…One of the best studied is the TFIIIA transcription factor, which contains zinc finger modules specialized for either DNA or RNA recognition. Some of these modules provide the majority of the protein binding affinity for DNA, whereas the others form specific complexes with their RNA targets (47)(48)(49). Thus, zinc fingers differ somewhat in ability to bind tightly to DNA and RNA.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, using a GAL4 one-hybrid system, we demonstrate that functional interaction between KLF6 and Sp1 requires the C-terminal domain of Sp1. Previous studies 55,56 provide ample evidence that Krüppel-like factors can interact with one another, typically involving the DNA binding domains. 52,53,57,58 KLF6 is induced as an immediate-early gene in hepatic stellate cells, the key cell regulating extracellular matrix production during tissue repair.…”
Section: Discussionmentioning
confidence: 99%
“…Zinc fingers 1, 2, and 6 may have other functions. By extrapolation from the function of the DNA nonbinding fingers in other zinc finger proteins, zinc fingers 1, 2, and 6 may contribute to the conformation of the protein by interacting with the DNA binding fingers, or they may be involved in nonspecific protein-DNA interactions, RNA binding, or nuclear localization signaling (8,12,31,38,40,41,46). Previous high-resolution structural studies indicated that C 2 H 2 -type zinc fingers bind exclusively in the major groove (36).…”
Section: Discussionmentioning
confidence: 99%